Simulation and experimental analysis of rolling element bearing fault in rotor-bearing-casing system. (October 2018) - Yang, Yizhou; Yang, Wenguang; Jiang, Dongxiang
Abstract: The rotor-bearing-casing system is an important structural form in aero-engines, where the main shaft bearing plays an important role in the safe and efficient operation of the whole engine. To study the performance of rolling element bearing faults and their transmission characteristics, a dynamic model of rotor-bearing-casing system with a nonlinear rolling element bearing is established in this paper. The rotor and the casing are modelled by finite element method and the rest parts are modelled by lumped mass method. The casing part is built using a kind of 2-D curved beam element. Single and mixed localized bearing defects are simulated in this dynamic model and also introduced in the rotor-bearing-casing system test system, then vibration signals from the bearing pedestal and the casing are obtained and analyzed. The simulation has a good prediction in components of bearing fault characteristic and modulation frequencies, which could be extracted from the experimental signals. Results are compared between the bearing pedestal and the casing, also between the simulation and the experiment. And sensitivity analysis could be conducted based on fault feature extraction and analysis at different locations on the flexible casing. Highlights: A dynamic model of rotor-bearing-casing system with a nonlinear rolling element bearing and a flexible casing is established. Single and mixed localized bearing faults are introduced into the simulation and the experiment. Typical fault features are predicted in the simulation and extracted in the experiment. Sensitivity of bearing faults at various points on the casing are analyzed.